Diagnostic and Management Challenges of Congenital Dia-phragmatic Hernia in Preterm Newborn: A Case Report in Remote Area, Asmat, South Papua - Priska Priyanka Maluenseng; Kevin Pieter Toman; Adinda Bunga Syafina (MAGNA MEDIKA Berkala Ilmiah Kedokteran dan Kesehatan, 2026)
Background: Congenital diaphragmatic hernia (CDH) is a rare condition associated with pulmonary complications, as the herniation of abdominal viscera into the chest can impact lung development. The majority of CDH newborns have respiratory issues at delivery or shortly after and require mechanical ventilation, which puts them at risk when they are transferred to a tertiary hospital for more extensive treatment.Objective:This article presents a case of a preterm infant with low birth weight with CDH managed in the General Hospital, Asmat Regency.Case Presentation:A male, born preterm at the gestational age of 31 weeks by spontaneous vaginal delivery, with a birth weight of 1505 grams. The patient had respiratory distress and required invasive ventilation shortly after delivery. When the patient showed improved oxygenation with a nasal cannula, we did a chest X-ray and detected bowel loops in the left hemithorax and mediastinal shift to the right. CDH treatment must be administered in tertiary hospitals to receive standard protocols and multidisciplinary treatment. Transferring the patient to a tertiary hospital requires continuous ventilation on full-day transportation, but the patient was not transportable; thus, we decided to operate. Significant progress was observed three months following the operation.Conclusion: CDH requires a CT scan for definitive diagnosis, an operative procedure, and intensive treatment in a tertiary hospital. Despite the limited resources and no referral options, the patient showed clinical improvements.